Introduction - Svatoň, Vladimír (Iluminace, 1995)
Introduction to the conversation between Yuri Civjan and Mikhail Yampolsky with Yuri Lotman, a leading representative of the semiotic school in Tartu, Estonia.
Keywords: Yuri Lotman; film semiotics